Evaluating the Kerma coefficients relevant to various water-equivalent materials at different photon energies - Zahra Abdi; Hamid Reza Baghani; Reza Shamsabadi (Nuclear Engineering and Technology)
To investigate the water equivalency of some solid phantoms, relevant Kerma coefficients were determined through both Monte Carlo (MC) simulation and analytical approaches over a wide range of photon energies ranging from 1 keV to 20 MeV.MCNPX MC Code was employed to simulate the Kerma coefficients for A-150, PMMA, Polystyrene, Solid Water (RMI 457), Solid Phantom (RW3), Virtual water, Solid Water (WT1), and Water Equivalent (Wte) solid phantoms. Kerma coefficients were also theoretically calculated using the mass energy absorption coefficients at different photon energies ranging from 1 keV to 20 MeV. Obtained Kerma coefficients for considered solid phantoms were also compared with those of water to find which material shows the best water-equivalency.Calculated Kerma coefficients by MC simulation were in a good agreement with those calculated via an analytical method which no statistically significant differences were observed among simulated and analytically calculated Kerma coefficients (p-value>0.05). Solid water (RMI 457) showed the best water-equivalency among studied plastic phantoms for radiology and radiotherapy quality assurance purposes. From the results, the Kerma coefficients for solid phantoms are highly dependent on photon energy.